Comunicação de marketing digital -um estudo junto a Vinícola Dom Victor - Cotica, Jonas (2023)
Digital marketing has assumed significant importance in companies' communication strategies, given its ability to interact with different audiences, increase brand visibility and enhance product purchases. This study aims to identify which digit al marketing strategies can contribute to improving brand visibility and increasing sales of Vinícola Don Victor products. To this end, a qualitative exploratory research was chosen, using in depth interviews with the owner and manager of Vinícola Dom Vict or, as well as secondary data analysis of company documents. The results of the study demonstrate that the company in question has a deficiency in relation to marketing communications, as it does not have a breakdown of actions that could contribute to lev els of knowledge, brand recall and customer acquisition. It is worth noting that the company remains firm in the production and marketing of wines and other products derived from grapes, adopting “old” marketing to promote its product mix. However, in the digital era, it is necessary for entrepreneurs to review some marketing concepts and start adopting digital marketing, which is currently so widespread through social networks. It was also found that the company does not have a defined Mission, Vision and Values. Finally, it was possible to verify that digital marketing has not yet been adopted by entrepreneurs, due to a lack of knowledge and not knowing how to deal with digital technologies. This demonstrated that there is interest in investing in digital marketing, without abandoning the marketing that had already been adopted since the founding of the Winery. In view of the findings, an Action Plan was drawn up, which will be delivered to the owners, as a suggestion for improvements to be implemented in t he company.